COMPARATIVE INDICATORS OF THE PHYSICAL DEVELOPMENT OF BOYS IN REPUBLIC OF DAGESTAN IN THE VARIOUS ECO-GEOGRAPHICAL ZONES - K. G. Kamalov; E. M-R. Soltakhanov; S. A. Abusuev; G. A. Gazimagomedov (Исследования и практика в медицине, 2015)
Abstract:Purpose. The examination of the comparative aspect of the physical parameters of the boys in the pre - and puberty in different ecological zones (EZ) of the Republic of Dagestan (RD): mountain, foothills and plains of the taxiway.Materials and Methods. The study in 3 eco-geographic zones of the Republic of Dagestan in 2641 a boy aged 11 to 17 years. Inclusion criteria were: age of onset of puberty and the completion of 11-17 years, male gender and residence in the territory (extragenital diseases). We compared the following anthropometric indicators: height, weight, body mass index.Results and conclusions. The analysing of the physical parameters of development in different areas of extragenital diseases RD identifies the following pattern: the lowest height and weight were boys living in the foothills of the taxiway. Their peers living in highland and lowland extragenital diseases taxiway growth were similar and statistically significant differences were found statistically significant differences are particularly evident with 13-14 years in boys from foothills of RD, especially when compared with their peers plain COPIES. Thus, the overall physical development of boys RD closes to those boys Russia, although the tendency to reduce them was determined. Comparative physical development of boys in various extragenital diseases RD, the worst performance demonstrated teenagers from foothill extragenital diseases.